Rate-Regulated Enterprises and Mandated Accounting Changes: The Case of Electric Utilities and Post-Retirement Benefits Other than Pensions (SFAS No. 106). - D'Souza, Julia M. (The Accounting Review, 1998)
This paper investigates the reporting and contracting responses of electric utilities to SFAS No. 106. Expense-increasing accounting standards generally have no direct cash flow consequences for nonregulated firms, but they reduce these firms' reported net income and increase their reported liabilities. Past research documents that managers of nonregulated firms seek to avert potential contracting costs associated with such mandated accounting changes through operating, financing or reporting decisions that mitigate the financial statement impact of the accounting change. In contrast, expense- increasing accounting standards do not usually affect rate-regulated firms' net income, but do have a positive effect on their cash flows because the rate recovery mechanism is based on accounting numbers. Managers of rate- regulated firms therefore have incentives to respond to expense-increasing accounting standards in ways that enhance the financial statement impact of the accounting change. This study documents that managers of rate-regulated firms that face greater uncertainties about future rate recoveries have greater incentives to use discretionary choices that intensify the impact of expense- increasing accounting changes on current financial statements.